Role of interpregnancy cervical encerclage in case of intrauterine insemination pregnancy - Tanksale, Shreedevi; Nadkarni, Purnima; Nadkarni, Aditi; Nadkarni, Pooja; Singh, Prabhakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cervical encerclage was first performed in 1902 in women with history of mid trimester abortion spontaneous preterm birth suggestive of cervical insufficiency, with the aim of preventing recurrent loss. Cervical insufficiency occurs in only 0.1% to 2% of all pregnancies. Cervical insufficiency has been defined as the inability of the uterine cervix to retain a pregnancy. Women with cervical insufficiency usually present with repetitive painless second trimester losses. There has not much been reported about cases in which interval cervical encerclage was done in non-pregnant state before start of ART procedure. We report a case with cervical insufficiency in a case of subseptate uterus who underwent interval cervical encerclage and carried pregnancy till term with positive outcome.